IMPLEMENTASI SERVICE EXCELLENCE OLEH CUSTOMER SERVICE PADA BANK SYARIAH MANDIRI KANTOR CABANG AMBON - Kamarudin, Ode (Institut Agama Islam Negeri (IAIN) Ternate, 2021)
The purpose of this study is to determine the process of service excellence by customer service in the service process at Bank Syariah Mandiri Ambon Branch Office and to determine the implementation of service excellence by customer service in the service process at Bank Mandiri Syariah Ambon Branch Office. The main problem in this study is how to implement service excellence standards for services that actually occur at Bank Mandiri Syariah Ambon Branch Office which is carried out by customer service. This type of research is field research by taking the research location at Bank Mandiri Syariah Ambon Branch Office using a qualitative approach. The data in this study consisted of primary data and secondary data obtained by using the interview method (interview) with customer service, documentation, and observation. The results of the study indicate that customer service can implement the standards set by Bank Syariah Mandiri Ambon Branch Office into services that have become their duties, (service excellence) which includes basic aspects of Accountability (Responsibility), Action (Actions), Attention (Attention), Appearance, Attitude, Ability that can satisfy and attract customers to remain loyal to Bank Mandiri Syariah Ambon Branch Office.